Exposure to multiple accents of English in the English Language Teaching classroom: from second language learners' perspectives. Issue 3 (1st September 2016) - Sung, Chit Cheung Matthew
Abstract : As a result of the global presence of English as a Lingua Franca (ELF), it has been argued that learners of English should be exposed to a range of varieties of English, rather than a single variety of English, so that they can be better prepared to communicate with other people in ELF communication. However, little is known about second language (L2) learners' perspectives on exposure to multiple accents of English in the English Language Teaching (ELT) classroom. This paper reports on a study that investigated the views of L2 learners of English concerning exposure to different accents of English in the classroom. Data were collected by means of semi-structured interviews and a questionnaire survey at a university in Hong Kong. The analysis revealed that these L2 learners showed rather ambivalent attitudes towards exposure to different accents of English in the classroom. While many participants seemed to be aware of the value of exposure to different native and non-native accents, there was less than wholehearted support for such a proposal in practice because of a number of pedagogical and practical concerns. Implications of the findings for classroom teaching are also discussed.